Simple full-wave model of E-plane waveguide star junction - Chumachenko, VP (Vsp Bv, 2002)
A full-wave electromagnetic model of a symmetrical star junction of N rectangular waveguides coupled in E-plane is presented. The model is based on a simple trigonometric-series expansion that is constructed for the field in the connecting region using the domain product technique and symmetry properties of the geometry. Before solving the final system of algebraic equations, all mathematical manipulations are carried out analytically without any numerical procedure. The analysis is applied to scattering characteristics of the junction. The validity and efficiency of the solution are verified by computational and comparison tests. The obtained frequency dependencies of S-matrices are presented for N = 3 to N = 7.
Keywords: Guide Junction; N-Port; Boundary; Cavity